Unmasking Cryoglobulinemia: A Cold-Blooded Complication of Hepatitis C - Alexandra M. Arges; Ari Levine (Case Reports in Hepatology)
A 43-year-old man presents to the hospital with two weeks of persistent fevers, accompanied by myalgias, hematochezia, and abdominal pain. Acute infectious causes were ruled out, and elevated inflammatory markers suggested inflammatory diarrhea or autoimmune conditions. Esophagogastroduodenoscopy (EGD) and colonoscopy were negative. Further testing showed positive antinuclear antibodies (ANAs), ribonucleoprotein (RNP), rheumatoid factor (RF), and hepatitis C virus (HCV) RNA, suggesting an HCV-associated autoimmune process. Hematuria and neuropathic pain raised suspicion for mixed cryoglobulinemia secondary to HCV, supported by low complement levels. Treatment started with prednisone. Cryoglobulins came back positive, confirming mixed cryoglobulinemia secondary to HCV. The patient was referred to the hepatology clinic for antiviral treatment, where he completed treatment, with symptoms resolving, except for his neuropathy.